The Genetic Evolution of Treatment-Resistant Cutaneous, Acral, and Uveal Melanomas - Makohon-Moore, Alvin P; Lipson, Evan J; Hooper, Jody E; Zucker, Amanda; Hong, Jungeui; Bielski, Craig M; Hayashi, Akimasa; Tokheim, Collin; Baez, Priscilla; Kappagantula, Rajya; Kohutek, Zachary; Makarov, Vladimir; et al. (Clinical cancer research, 2021)
Melanoma is a biologically heterogeneous disease composed of distinct clinicopathologic subtypes that frequently resist treatment. To explore the evolution of treatment resistance and metastasis, we used a combination of temporal and multilesional tumor sampling in conjunction with whole-exome sequencing of 110 tumors collected from 7 patients with cutaneous ( = 3), uveal ( = 2), and acral ( = 2) melanoma subtypes. Primary tumors, metastases collected longitudinally, and autopsy tissues were interrogated. All but 1 patient died because of melanoma progression. For each patient, we generated phylogenies and quantified the extent of genetic diversity among tumors, specifically among putative somatic alterations affecting therapeutic resistance. In 4 patients who received immunotherapy, we found 1-3 putative acquired and intrinsic resistance mechanisms coexisting in the same patient, including mechanisms that were shared by all tumors within each patient, suggesting that future therapies directed at overcoming intrinsic resistance mechanisms may be broadly effective.